2017
DOI: 10.1080/10717544.2017.1419514
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of injectable Rasagiline mesylate dual-controlled drug delivery system for the treatment of Parkinson’s disease

Abstract: A microsphere–gel in situ forming implant (MS–Gel ISFI) dual-controlled drug delivery system was applied to a high water-soluble small-molecule compound Rasagiline mesylate (RM) for effective treatment of Parkinson’s disease. This injectable complex depot system combined an in situ phase transition gel with high drug-loading and encapsulation efficiency RM–MS prepared by a modified emulsion-phase separation method and optimized by Box–Behnken design. It was evaluated for in vitro drug release, in vivo pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Pharmacokinetic studies in healthy Chinese populations showed that the transdermal rasagiline patch was able to prolong the duration of administration with good safety and tolerability, providing a continuous treatment modality for patients who were not able to routinely take oral medications [ 133 ]. Furthermore, animal studies showed that injectable rasagiline based on an injectable long-acting formulation system significantly increases dopamine levels in PD model rats ( p < 0.05) and effectively improves motor symptoms [ 134 ]. Encapsulation rasagiline in polycaprolactone microspheres prolonged drug release for 1 month by a single subcutaneous dose, and no significant difference was found with daily rasagiline administration in animal studies [ 135 ].…”
Section: Future Of Mao-b Inhibitorsmentioning
confidence: 99%
“…Pharmacokinetic studies in healthy Chinese populations showed that the transdermal rasagiline patch was able to prolong the duration of administration with good safety and tolerability, providing a continuous treatment modality for patients who were not able to routinely take oral medications [ 133 ]. Furthermore, animal studies showed that injectable rasagiline based on an injectable long-acting formulation system significantly increases dopamine levels in PD model rats ( p < 0.05) and effectively improves motor symptoms [ 134 ]. Encapsulation rasagiline in polycaprolactone microspheres prolonged drug release for 1 month by a single subcutaneous dose, and no significant difference was found with daily rasagiline administration in animal studies [ 135 ].…”
Section: Future Of Mao-b Inhibitorsmentioning
confidence: 99%
“…In-situ forming implants (ISFIs) are sustained drug delivery systems consisting of a biocompatible, water-miscible solvent such as N-methyl-2-pyrrolidone (NMP) or dimethyl sulfoxide (DMSO) and a biodegradable polymer, most commonly a polyester such as PLGA [1][2][3][4]. The water-miscible solvent is used to dissolve both the polymer and drug to form a liquid formulation that can be injected into the intramuscular or subcutaneous space [5][6][7]. The implant is formed via phase inversion, during which the water-miscible solvent diffuses from the ISFI into the aqueous injection site, leaving the precipitated polymer to trap the drug in a solid matrix [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The potential applications of MPs and NPs for PD therapy have been explored in the last few years for different drugs, such as levodopa [ 12 , 13 ], rasagiline [ 14 , 15 ], puerarin [ 16 ], schisantherin A [ 17 ], glial cell line-derived neurotrophic factor (GDNF) [ 18 ], ropinirole [ 19 ], and apomorphine [ 20 ].…”
Section: Introductionmentioning
confidence: 99%